The legal rights and responsibilities of teachers : issues of employment and instruction - Osborne, Allan G. (Corwin, 2011)
Most teacher education programmes offer little, if any instruction on education law. In light of this dearth of information about law, this book is designed as an easy-to-read practical manual that addresses the key legal issues that teachers confront on a daily basis.